From Cradock, With Love: Affective Substantive Post -Apartheid Citizenship for Women of Colour - Elder, Emily (Department of Sociology, 2014)
This qualitative case study examines conceptualizations of post-apartheid democratic citizenship. Drawing on in-depth, semi-structured interviews conducted in July 2009 with twelve voting age women of colour in the small town of Cradock in the Eastern Cape, it demonstrates how traditional theorizations are inadequate for understanding the substantive citizenship some small town women desire, live, and demand. Though the research design began with a traditional definition that citizenship rests on the knowledge of and ability to engage with claiming rights findings demonstrated the failings, and challenged the sufficiency, of this approach. Listening closely to the voices of the women interviewed revealed the importance of emotion. Further, the ways that emotion emerged from these interviews illuminate an under-examined aspect of substantive citizenship: its affective dimensions. The affective issues that emerged were those of perceived elite indifference to the people, conflicted feelings about the post-apartheid state, racialized and gendered hatred and hate speech, and the women's hopes for an ideal public life based on love and respect. Working from a race-conscious, post-colonial, feminist lens, I argue that while a rights-based approach to citizenship is necessary, it cannot fully encompass the complexities of post-apartheid substantive citizenship, especially for small-town women of colour. Considering affect leads to a more meaningful theory of citizenship, one that must rest on a loving, political ethic.